Caregiver satisfaction and its associated factors in pediatric wards of Jimma University Medical Center, Southwest Ethiopia - Mohammed Beshir; Tsion Tilahun; Diriba Fufa Hordofa; Gersam Abera; Workineh Tesfaye; Kumale Tolesa Daba; Netsanet Workineh; Samson Nadew Woldeyesus; Tilahun Fufa Debela; Elias Ali Yesuf (BMC, 2022)
Abstract Background Measuring the caregivers' satisfaction is vital for the effectiveness of childcare. Children admitted to pediatric wards require special hospital situations, a bespoke approach from the medical team, and the participation of caregivers. It is important to give attention to the caregivers while planning for child services. The purpose of this study was to assess the caregiver's satisfaction with the services provided in pediatric wards of Jimma University Medical Center and identify its associated factors. Methods Facility-based cross-sectional study design was done at Jimma University Medical Center. Participants in the study were primary caregivers who spent two or more days in the pediatric ward with their admitted children. Data were collected from 400 selected caregivers. A consecutive sampling method was employed. Principal component analysis was done for all Likert scale instruments to extract factor (s) representing each of the scales and to have factor scores. Variables with the Likert scale were treated as continuous after principal component analysis was employed. Using these factor scores, a multiple linear regression analysis was carried out to identify factors associated with caregivers' satisfaction with service in pediatric wards. A significance level of less than 0.05 was used in the final model to determine statistical significance. Result This study showed that caregivers' satisfaction with the services in the pediatric ward was 68%. Level of education (β = -0.24, (95% CI; -.411, -.070)), availability of basic facilities (β = 0.163, (95% CI; .063, .263)), patience to listen to patients' problem (β = 0.431, (95% CI; .324, .537, staff communication with client (β = 0.163, (95% CI; -4.839, -1.610)), availability of laboratory tests and its service (β = -0.964, (95% CI; -1.435, -.493)), availability of drug, imaging and service at radiology (β = 2.907, (95% CI; 1.470, 4.344)) and availability of pathology and its service (β = 1.869, (95% CI; .993, 2.746)) were significant factors associated with caregivers satisfaction with health service in pediatrics ward. Conclusion Caregivers were moderately satisfied. Education level, availability of basic facilities communication with client, and the availability of laboratory tests and drugs were factors that significantly associated with caregiver satisfaction. Hospital should avail laboratory tests and drugs in order to maintain high levels of caregiver satisfaction.